A Review On Airborne Particulate Soiling Defect On Users And Artefacts In The Museum Environment - Mohd Din, Shamzani Affendy; Muhsin Kolapo, Otuyo; Osman, Sharina; Azam Adnan, Muhamad; Jawahir Raduian, Nor (Opción, 2019)
Recent studies have reported soiling defects and health hazard caused by particulate matter, poor Indoor Air Quality (IAQ) conditions, and damages caused by varying microclimate conditions in the museum. When airborne particulates combine with various substances in the air, a chemical reaction occurs, which results in the formation of inorganic and organic compounds. These compounds are then deposited on the surfaces of artefacts which reduces the aesthetic properties and value of the artefacts through a process known as soiling. Additionally, airborne particulates can trigger various health effects on museum users. Such as cough, sneezing, lungs irritation, itchy eye, cancer, heart attack, and can lead to death. Purpose: This research is, therefore aimed at reviewing the recent trends in countries annual mean concentration of Particulate matters, characteristics of museum collections, sources of Particulate Matter in the museum, and its effect on artefacts and museum users, and concentration and chemical com- positions of airborne particulate in Finding: Several studies have been published in relating to the concen- tration and chemical compositions of airborne particulates in Europe and Asia. However, detailed research is still lagging on the composition of Airborne particulate in Malaysian Implication: Therefore, more research needs to be conducted based on this research gap to enable risk assessment inside Museum Environment.